A erística da moeda e a crise do sistema financeiro e monetário internacional - Alves Filho, Olinto Silveira (2016)
In this doctoral work were shown some questions about the phenomenon here called monetary eristic, notably those related to the nature and form of money, its origin, its functions etc., but also those related to the dynamics and the development of capitalism in the context the crisis of the financial system and the international monetary (and its dominant currency, the US dollar), so that your goal is to understand to what extent the theoretical controversies about the currency have borne out the old Keynesian thesis on the creation of an international currency. The analysis focused on a very particular form of monetary eristic, explained the following question: how the current crisis of the financial system and the international monetary, in the last 16 years (2000-2015), has motivated the theoretical controversies about the currency and raised the debates on the old Keynesian thesis of creating an international currency? To think about the problem, served up an exploratory research, resorting to bibliographic and documentary research, which is why, among the documentary pieces here analyzed are the Proceedings and Documents of the United Nations Monetary and Financial Conference - Bretton Woods, New Hampshire, July 1-22. Money is, in fact, a social relationship and modern capitalist society is molded ideologically as expected wealth and, therefore, material expression and symbolic of capital accumulation processes and concealment of the exploitative relations and power of the ruling bourgeois class. In the late twentieth century it was consolidated the triad composed of the restructuring process, by neoliberalism and the financial globalization that has shaped the new phase of global geopolitics. This, in turn nurtured the unfinished and monumental first crisis of the capitalist mode of production of this century (born in the American furniture market, subprime in 2008). So that such a crisis, by its nature and dynamic, motivated even by the need to find alternatives for their solution, placed in the center of theoretical debates, controversies about the US dollar (legitimacy and confidence crisis), giving rise, as one of many possible alternatives, the old Keynesian thesis of creating an international currency.